A new tree frog in the genus Polypedates (Anura: hacophoridae) from southern Thailand - Rujirawan, Attapol; Stuart, Bryan L.; Aowphol, Anchalee (Zootaxa, 2013)
We describe a new species of Southeast Asian rhacophorid frog belonging to the Polypedates leucomystax species complex from Songkhla Province, southern Thailand. Polypedates discantus sp. nov. is distinguished from its congeners by the combination of having the skin of the head not co-ossified with the skull; absent or indistinct white dots on the back of the thigh; paired-vocal sac openings; and a round tubercle on the tibiotarsal articulation. The new species is also distinguished from P. leucomystax and P. megacephalus in univariate and multivariate analyses of quantitative morphometric characters, and has uncorrected pairwise distances of 6.61–7.16% from its closest relative, P. leucomystax, in the mitochondrial 16S rRNA gene. The new species has four distinct male advertisement call types, consisting of one-note, two-note, three-note and staccato calls. The new species occurs syntopically with P. leucomystax at the type locality.